2019
DOI: 10.1149/2.0451908jes
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Enabling Extreme Fast Charging of High Energy Density Li-Ion Cells while Avoiding Lithium Plating

Abstract: To improve electric vehicle market acceptance, the charge time of their batteries should be reduced to 10-15 minutes. However, achieving 4C to 6C charge rates with today's batteries is only possible for cells with thin electrodes coming at the expense of low energy density and high battery manufacturing cost. An electrochemical model is validated versus high rate charge data for cells with several loadings. The model elucidates that the main limitations for high energy density cells are poor electrolyte transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
216
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(226 citation statements)
references
References 33 publications
6
216
0
Order By: Relevance
“…Of note, the ANL authors found that Li plating did not cause measurable discharge capacity loss for currents up to 6C for the conditions studied (see their discussion associated with figure 5 of [7]), despite the fact that their reference electrode measurement confirmed Li plating at the graphite electrode. Recent analyses [7][8][9][10][11][12] of lithium plating underscore its technological relevance. In [13], the authors developed a set of equations that can be used to treat Li plating and subsequent electro-dissolution in the context of a porous electrode, and simulations were provided for a single-particle model, which ignores all impedances associated with the electrolyte phase and considers each particle in the porous electrode to be identically spherical and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the ANL authors found that Li plating did not cause measurable discharge capacity loss for currents up to 6C for the conditions studied (see their discussion associated with figure 5 of [7]), despite the fact that their reference electrode measurement confirmed Li plating at the graphite electrode. Recent analyses [7][8][9][10][11][12] of lithium plating underscore its technological relevance. In [13], the authors developed a set of equations that can be used to treat Li plating and subsequent electro-dissolution in the context of a porous electrode, and simulations were provided for a single-particle model, which ignores all impedances associated with the electrolyte phase and considers each particle in the porous electrode to be identically spherical and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…17 Li plating becomes more favorable at higher SOC for a number of reasons, including: the buildup of Li + concentration gradients over time that leads to higher overpotentials near the electrode-separator interface, the decrease of graphite solid state Li diffusion coefficient with increasing Li content, and intraparticle lithiation gradients that result in LiC6 near surface which prevents further intercalation. 25,26 Coulombic efficiency (CE) analysis of the plating onset cycling in Fig. 2c provides strong evidence that dOCV signals correspond to Li plating instead of other graphite phase relaxation processes.…”
Section: Resultsmentioning
confidence: 92%
“…The generated heating inside the cell is not completely uniform because the electronic resistance, ionic resistance, and electrochemical reaction static resistance inside the cell are also unevenly distributed, which is accelerated in a fast-charging state. Further study showed that the heat generation normalized of each cell in the pack is approximately 30% greater than that for a single cell, as shown in Figure 4a [14]. The resistance between conductors and plug-ins is also relatively high in fast-charging battery systems.…”
Section: Bms Designmentioning
confidence: 98%
“…To support the fast-charging performance of the cell, considerable effort goes into the design of a single cell battery pack. Generally, the fast-charging performance of a single cell can be improved by adding more conductive agent to the electrode [11], reducing the loading of the electrode material (thinner coating), using a thicker collector, adjusting the suitable tab position, retaining a larger electrode porosity [12,13], ensuring less electrode bending [14], etc. These methods can improve the kinetic and electrical properties and reduce the internal resistance of cells.…”
Section: Battery/battery Pack Designmentioning
confidence: 99%
See 1 more Smart Citation